Homo Oeconomicus and Behavioral Economics - Justyna Brzezicka; Radosław Wisniewski (Contemporary Economics)
Recent years have witnessed a growing interest in behavioral trends in both economic theory and practical applications. As a science with vast potential for explaining complex market behaviors, behavioral economics is drifting away from the classical model of homo oeconomicus deployed by mainstream economics. This paper discusses the significance and role of the homo oeconomicus model in light of behavioral economics. It analyzes the direction of changes affecting homo oeconomicus, examines the definition of anomalies within the context of behavioral economics and discusses the anomalous status of homo oeconomicus. The paper proposes a hypothesis that the attitude characterizing homo oeconomicus is unique and incidental. The presented interdisciplinary analysis relies on economics, behavioral economics, economic psychology, behavioral finance and the methodology of science to discuss the homo oeconomicus model. The paper reviews change trends in economics, which are largely propelled by advancements in behavioral economics. The key methodological tools deployed in this paper are theoretical analysis and a compilation of extensive research findings. The results were used to formulate new theories advocating the development of a modern approach to the homo oeconomicus model, recognizing its significance and the growing importance of behavioral economics.